International Instruments in Administrative Decisions: Mainstreaming International Law - Poole, Melissa (Victoria University of Wellington Law Review, 1999)
This article considers the development of the role of international instruments in administrative decisions. It compares the changes in New Zealand after the Tavita case with the developments which followed the Teoh case in Australia. The article then proposes the basis for a new attitude to international instruments which would result in the "mainstreaming" of international law.